ANALISIS BAI’ GHARAR TERHADAP JUAL BELI FOLLOWER DI INSTAGRAM - Nahdiah Nahdiah; Syarif Hidayatullah (Jurnal Al-Mizan, 2019)
Instagram is one of the social media application that is widely used, Instagram users competing to have a large number of followers to follow the trend and to do business on Instagram, so many offer follower buying and selling in order to have a large number of followers in a short time. However, buying and selling followers on Instagram is controversial whether it is in accordance with the terms of buying and selling in Islam, or there is a bai gharar element contained in buying and selling followers on Instagram. This research uses qualitative research. Data from this study were collected from direct interviews with buyers and sellers of followers as well as with Dewan Syariah Nasional Majelis Ulama Indonesia (DSN-MUI) members, as well as supporting literature relevant to the issues raised by the author. Then analyzed by the writer using descriptive analysis. The results of this study are the buying and selling of followers containing the baiʽ gharar element if the seller sells a fake account and if he gets the account without prior permission and gets it without going through the application. Buying and selling legal follower may be as long as it does not contain elements of gharar, and the allotment of lawful and harmonious conditions and conditions have met the provisions of the Shari'a, but if it contains elements of gharar then buying and selling followers become haram.